Identification of metabolites of dalfampridine (4-aminopyridine) in dog and rat. (23rd April 2013) - Caggiano, Anthony; Blight, Andrew; Parry, Tom J.
Abstract: Background: Dalfampridine (4-aminopyridine; 4-AP) is a potassium channel blocker available in the United States to improve walking in patients with multiple sclerosis as demonstrated by an increase in walking speed. Its pharmacokinetics have been evaluated in human studies but its metabolites are not well characterized. This study characterizes the metabolic profile of dalfampridine in two animal species that were used to support nonclinical toxicology evaluation. Methods: Metabolic profiling of single oral 14 C-4-AP doses was performed in 12 adult male Sprague–Dawley rats. Similarly, metabolic profiling was performed in beagle dogs in two studies that administered 14 C-4-AP by gastric intubation; the first study included six animals (three males, three females), and the second study included two animals (one male, one female). Blood and urine samples were evaluated using high performance liquid chromatography, thin layer chromatography, and radioanalysis (liquid scintillation counting), with further identification of components by gas chromatography/mass spectrometry. Results: Five radioactive components, M1–M5, were detected in rat plasma, although most of the radioactivity corresponded with unchanged 4-AP. Based on Rf values, M1 and M2 coseparated with reference standards of 3-hydroxy-4-AP and 4-AP, respectively. Additionally, components M1, M2, and M3 coseparated with the same components isolated from the urine of a dog dosed with 14 C-4-AP and identified as 3-hydroxy-4-AP, 4-AP, and 3-hydroxy-4-AP sulfate, respectively; M4 and M5 could not be identified because of low concentrations. In dogs, most of the radioactivity was excreted within the first 24 hours as unchanged compound. Conclusions: Following oral dosing, 4-AP was rapidly absorbed in rats and dogs, with rapid excretion and almost complete urinary recovery in dogs. The primary metabolites in both animal models were 3-hydroxy-4-AP and 3-hydroxy-4-AP sulfate. Systemic clearance not accounted for by renal excretion of 4-AP may occur by liver metabolism by hydroxylation of 4-AP to 3-hydroxy-4-AP followed by sulfate conjugation to 3-hydroxy-4-AP sulfate.